2021
DOI: 10.1021/acs.est.1c04716
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Major Phthalate and Alternative Plasticizer Metabolites in Children of Thailand, Indonesia, and Saudi Arabia, and Associated Risks

Abstract: Phthalates are widely used in consumer products and are well-known for adverse endocrine outcomes. Di-(2-ethylhexyl) phthalate (DEHP), one of the most extensively used phthalates, has been rapidly substituted with alternative plasticizers in many consumer products. The aim of this study was to assess urinary phthalate and alternative plasticizer exposure and associated risks in children of three Asian countries with different geographical, climate, and cultural characteristics. Children were recruited from ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 82 publications
1
33
2
Order By: Relevance
“…A recent study reported 56% of human serum samples from a US population had detectable levels of DINCH metabolites [ 27 ]. In another study, alternate plasticizers have been detected in urinary samples of school kids from many countries, including Saudi Arabia [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported 56% of human serum samples from a US population had detectable levels of DINCH metabolites [ 27 ]. In another study, alternate plasticizers have been detected in urinary samples of school kids from many countries, including Saudi Arabia [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, associations with the low-molecular weight phthalates DMP and DEP were positive but very weak to non-existent (ρ ≤ 0.2) in all countries (Figure S1). Overall, the associations observed between NP and the plasticizers were much weaker than within the group of plasticizers in the very same population (Lee et al 2021) . There, correlations among high-molecular weight plasticizers were generally higher than or equal to ρ = 0.7 for DINP, DiDP, DINCH, and DEHTP with a similar cluster of higher associations for the low-molecular weight plasticizers.…”
Section: Resultsmentioning
confidence: 99%
“…This study has been approved by the Research Ethics Committees of King Saud University (CAMS 053-37/38), Mahidol University (MUTM2017-209-01), and Halu Oleo University (007/ECHR-IPHA/XII/2017). For details of sample collection and treatment, see Lee et al (2021) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations